Lubricating system capable of shortening oil outlet time of externally-hung oil pump - QIN MINGZHI; MO SHENGCHENG; LI WEI; ZHUANG SHANSHAN (2024)
The invention provides a lubricating system capable of shortening the oil outlet time of an externally-hung oil pump, and relates to the technical field of engine lubrication, the lubricating system comprises an oil pump and an oil tank, an oil pumping pipe is arranged on an inlet of the oil pump, the lower end of the oil pumping pipe is immersed in the oil tank, and the lubricating system further comprises a pre-supply pump; an inlet of the pre-supply pump is communicated with the upper end of the oil pumping pipe, and an outlet of the pre-supply pump is communicated with the oil tank. In the application, the pre-supply pump is additionally arranged at the inlet of the oil pump to assist the oil pump in pumping air in the oil pumping pipe between the pump and the liquid level in the oil tank, so that the oil pump can quickly pump oil, lubricating oil is conveyed to each kinematic pair of an engine in the shortest time, and the lubricating effect is improved. 本申请提供了一种可缩短外挂式机油泵出油时间的润滑系统，涉及发动机润滑技术领域，包括机油泵和油箱，所述